Evaluating Legal Measures, International Conventions, and Collaborative Strategies to Enhance Child Protection from Misinformation and Disinformation in the Digital Communication Landscape of Nordic Nations - Butt, Junaid Sattar (Acta Universitatis Danubius. Communicatio, 2024)
The digital world offers a wealth of information for children, but in today's digital age, children are increasingly exposed to misinformation and disinformation, posing significant challenges to their well-being and development. In the Nordic states, renowned for their progressive digital infrastructure and commitment to child welfare, addressing this challenge has become a focal point of policy discussions and scholarly inquiry. This research manuscript delves into the nuanced landscape of child protection from misinformation and disinformation within the digital communication sphere of Nordic nations. This research investigates the effectiveness of current legal measures, international conventions, and collaborative strategies in safeguarding children from this harmful content. Drawing upon a multidisciplinary approach, this manuscript scrutinizes existing legislative frameworks and policy initiatives aimed at mitigating the dissemination of harmful content targeting children. Furthermore, it investigates the alignment of these measures with international conventions and treaties pertinent to child rights and digital safety. Moreover, this research explores collaborative strategies among stakeholders, including governments, non-governmental organizations, tech companies, educators, and parents, in fostering a safer digital environment for children. By analyzing best practices and innovative interventions, this manuscript offers insights into effective mechanisms for detecting, addressing, and preventing the proliferation of misinformation and disinformation targeting children. Ultimately, this research contributes to the advancement of evidence-based policies and interventions tailored to the unique challenges posed by misinformation and disinformation in the digital communication landscape of Nordic nations. It underscores the imperative of concerted efforts at the national, regional, and international levels to protect children's rights and well-being in an increasingly complex digital ecosystem.